EFFICIENCY OF MOBILE APPS IN HEALTHCARE: A CASE STUDY OF MED-UZ AI - Izbasarov Islomjon; Arzikulov Fazliddin (Modern American Journals, 2025)
The rapid advancement of mobile technology has transformed healthcare delivery, particularly in resource-constrained regions. This study explores the efficiency of mobile applications in healthcare, focusing on "MED-UZ AI," a mobile application developed to address healthcare challenges in Uzbekistan. MED-UZ AI leverages artificial intelligence (AI) to provide medical consultations, enhance health literacy, and ensure data security. By analyzing its functionality, target audience, and implementation strategy, this paper evaluates the app’s potential to improve healthcare accessibility, early diagnosis, and service quality. The findings highlight the role of mobile apps in bridging healthcare gaps, with implications for global health systems.
Keywords: Mobile healthcare, artificial intelligence, MED-UZ AI, health literacy, data security, Uzbekistan healthcare, telemedicine, digital health.